Hierarchical Group Authentication and Key agreement for Machine Type Communication in LTE Networks - Srinivas Kalime (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The 3GPP LTE-A standard for Machine Type Communication (MTC) was created to facilitate communication between entities without human involvement, in response to the rapid increase in wireless data communication volume. The conventional Mutual Authentication and Key Agreement (AKA) mechanism in LTE networks is struggling due to the rising signaling load caused by the expanding device count. Group-based architecture has been proposed as a solution in the literature to solve authentication traffic, but it has its own problems. In this paper, we propose a hierarchical group based mutual authentication and key agreement (HGMAKA) protocol to address these challenges. This protocol ensures privacy, prevents unauthorized access to information, and helps prevent many types of assaults such as replay attacks, distributed denial of service, and man-in-the-middle attacks. The proposed protocol enables MTC services to be supported by small cells with heterogeneous architecture that aligns with 5G networks. The Aggregate Message Authentication Code based approach is more lightweight, resource-efficient, robust against authentication message failures, and scalable to heterogeneous network topologies compared to earlier protocols. We experimented our proposed system and the results demonstrated increased efficiency, resolved existing difficulties, and will enhance the reliability and security of the M2M system.